Место отраслевой конкурентоспособности в системе национальной конкурентоспособности.A place of Branch Competitiveness is in the system of National Competitiveness. (Journal of Economic Research & Business Administration, 2015)
В статье приведены результаты исследования теоретико-методологических аспектов конкурентоспособности национальной экономики, отрасли, продукции. Конкурентоспособность национальной экономики рассматривается с позиции конкурентоспособности отрасли, а конкурентоспособность отрасли – с позиции конкурентоспособности продукции.The article presents the results of a study of theoretical and methodological aspects of the competitiveness of the national economy, industry products. National competitiveness is seen from the perspective of industry competitiveness, and competitiveness of the industry - from the perspective of competitiveness.